Safety and efficacy of a feed additive consisting of Bacillus velezensis PTA‐6507, B. velezensis NRRL B‐50013 and B. velezensis NRRL B‐50104 (Enviva® PRO 202 GT) for turkeys for fattening (Danisco Animal Nutrition) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2021)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of the additive consisting of Bacillus amyloliquefaciens PTA‐6507, B. amyloliquefaciens NRRL B‐50013 and B. amyloliquefaciens NRRL B‐50104 (trade name: Enviva® PRO 202 GT) for turkeys for fattening. The product under assessment is based on viable spores of three strains originally identified as B. amyloliquefaciens which, in the course of the current assessment, were reclassified as Bacillus velezensis. The bacterial species B. velezensis is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the active agents was established. The active agents do not harbour acquired antimicrobial resistance genes and lack toxigenic potential and the capacity to produce aminoglycosides. Following the QPS approach, the three bacterial strains are presumed safe for the target species, consumers and the environment. Since no concerns are expected from the other components of the additive, Enviva® PRO 202 GT is also considered safe for the target species, consumers and the environment. Enviva® PRO 202 GT is non‐irritant to skin and eyes and is not a dermal sensitiser. Due to the proteinaceous nature of the active agents, the additive should be considered a respiratory sensitiser. In a previous opinion, it was concluded that Enviva® PRO 202 GT has a potential to be efficacious as a zootechnical additive in chickens for fattening at the recommended level of 7.5 × 107 CFU/kg complete feed. It is considered that conclusions on efficacy of Enviva® PRO 202 GT in chickens for fattening can be extrapolated to turkeys for fattening. Therefore, the FEEDAP Panel concludes that Enviva® PRO 202 GT has the potential to be efficacious in turkeys for fattening at 7.5 × 107 CFU/kg complete feed.